Structural and functional heterogeneity in phloem loading and transport - Slewinski, Thomas L.; Zhang, Cankui; Turgeon, Robert (Frontiers in Plant Science, 2013)
The phloem is often regarded as a relatively straightforward transport system composed of loading (collection), long-distance (transport) and unloading zones. While this simple view is necessary and useful in many contexts, it belies the reality, which is that the phloem is inherently complex. At least three types of sieve element-companion cell complexes are found in minor veins of leaves. Individual species may have more than one type, indicating that they employ multiple loading strategies, even in the same vein. Gene expression data in particular points to heterogeneity in sieve element-companion cell complexes of minor veins, perhaps in all flowering plants. Phloem heterogeneity in the long-distance phloem is also evident in many species based on anatomical, biochemical and gene expression data. In this regard, members of the Cucurbitaceae are especially complex and interesting. We conclude that the phloem is highly intricate and that a hidden world of specialized function awaits discovery.